Political demand and policy advice: a framework for analysis. (4th July 2019) - Manwaring, Rob
ABSTRACT: In the policy advice literature, there has been two main "waves" of research focus. In the first wave, the focus of scholarly attention tended to focus on single policy advice actors. A key innovation was offered by Halligan, who sought to frame policy advice within a policy advisory system, with a focus on government control and location. In later research, Craft and Wilder called for a "second wave" of research which also sought to integrate factors such as policy content, context, ideational compatibility but also reflect the increasingly polycentric advice landscape. This article contributes to the second wave drawing attention to a key element of the institutional dynamics of policy advice systems, namely the issue of political "demand". A core argument offered in this article is that the dynamics of demand need to be interrogated more fully, and be given greater prominence in current understandings of PAS dynamics. The net effect of marginalizing "demand" factors is that it can de-politicize the extent and nature of advice-giving, and reduce it to a seeming technocratic exchange. To expand our understanding of demand, this paper offers a framework for understanding the dynamics of demand within policy advice systems.